2011
DOI: 10.5301/jn.5000022
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the salivary urea test as a method to diagnose chronic kidney disease

Abstract: The salivary urea test has a great capacity to discriminate patients with chronic kidney disease from healthy people, and it was shown that the best cutoff point is 40 mg/dL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
1
16
1
Order By: Relevance
“…Salivary urea[678917] and creatinine[1819] levels showed positive correlation with serum levels both in cases and controls. This finding is in accordance with the previous finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salivary urea[678917] and creatinine[1819] levels showed positive correlation with serum levels both in cases and controls. This finding is in accordance with the previous finding.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were obtained by other authors. [1920] However, comparatively, lesser values of sensitivity of 80%, specificity of 71%, PPV of 80%, and NPV of 71% were demonstrated by Zuniga et al .,[8] whereas sensitivity of 80%, specificity of 90%, and area under the curve of 0.898 in ROC were demonstrated by Xai et al . [6]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports in humans have found that urea and creatinine can be measured in saliva and that salivary concentrations of both analytes are positively correlated to plasma levels [8][9][10]. In addition, it has been suggested that analysis of salivary urea and creatinine can be used in the diagnosis of chronic kidney disease (CKD) and also for monitoring progression and efficacy of haemodialysis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced imaging techniques are just one of the several methods that can be used for early diagnosis of kidney involvement. It has been claimed that accurate analysis of salivary urea can be used as a proper tool in diagnosing of chronic kidney disease [149]. In addition, development of different imaging contrast agents improved the diagnosis accuracy of medical imaging techniques [15].…”
Section: Future Prospect: An Ideal Renal Imaging Modalitymentioning
confidence: 99%